2019
DOI: 10.1126/science.aav9713
|View full text |Cite
|
Sign up to set email alerts
|

Copper’s rapid ascent in visible-light photoredox catalysis

Abstract: Visible-light photoredox catalysis offers a distinct activation mode complementary to thermal transition metal catalyzed reactions. The vast majority of photoredox processes capitalizes on precious metal ruthenium(II) or iridium(III) complexes that serve as single-electron reductants or oxidants in their photoexcited states. As a low-cost alternative, organic dyes are also frequently used but in general suffer from lower photostability. Copper-based photocatalysts are rapidly emerging, offering not only econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
302
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(353 citation statements)
references
References 86 publications
3
302
1
10
Order By: Relevance
“…Although most of radical-Cu(II) rebound processes involved activated secondary or tertiary benzylic carbons [42][43][44] , we have very recently shown that it is also possible to functionalize the primary radical in the presence of copper under photocatalysis conditions 45,46 . While dual photocatalyst/Cu catalytic system has emerged as a powerful tool for cross-coupling reactions 47 , the catalytic cycle depicted in Fig. 1e using copper as the only catalyst remained uncommon [48][49][50][51] .…”
mentioning
confidence: 99%
“…Although most of radical-Cu(II) rebound processes involved activated secondary or tertiary benzylic carbons [42][43][44] , we have very recently shown that it is also possible to functionalize the primary radical in the presence of copper under photocatalysis conditions 45,46 . While dual photocatalyst/Cu catalytic system has emerged as a powerful tool for cross-coupling reactions 47 , the catalytic cycle depicted in Fig. 1e using copper as the only catalyst remained uncommon [48][49][50][51] .…”
mentioning
confidence: 99%
“…Seminal works by Kochi and co‐workers have shown that alkyl radicals rapidly react with Cu(OAc) 2 to generate putative metastable alkylcopper(III) species . More recently, such alkylcopper(III) species have been proposed as key intermediates in reactions exploiting dual copper/photoredox catalysis processes . Thus, in the early stage of the reaction, that is, when the Cu II concentration is still high, radical intermediate C might react with Cu(OAc) 2 to generate an alkylcopper species D , which may be viewed as a masked radical.…”
Section: Resultsmentioning
confidence: 99%
“…[13] More recently,s uch alkylcopper(III) species have been proposed as key intermediates in reactions exploiting dual copper/photoredox catalysis processes. [22] Thus, in the early stage of the reaction, that is, when the Cu II concentration is stillh igh, radical intermediate C might react with Cu(OAc) 2 to generate an alkylcopper species D,w hich may be vieweda samaskedr adical. This may be particularly important for limiting the polymerization in the early stage of the reaction, when the concentration of reducing Cu I/0 species is low.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, alternative solutions have to be developed. Among them, the use of first-row transition metals [8,9], particularly copper, is an interesting approach [10][11][12][13]. The high abundance, low price, low toxicity, and intrinsic properties (redox potential, four oxidation states, etc.)…”
Section: Introductionmentioning
confidence: 99%